FH535 Suppresses Osteosarcoma Growth In Vitro and Inhibits Wnt Signaling through Tankyrases - Gustafson, Carl T.; Mamo, Tewodros; Shogren, Kristen L.; Maran, Avudaiappan; Yaszemski, Michael J. (Frontiers in Pharmacology, 2017)
Osteosarcoma is an aggressive primary bone tumor which exhibits aberrantly activated Wnt signaling. The canonical Wnt signaling cascade has been shown to drive cancer progression and metastasis through the activation of β-catenin. Hence, small molecule inhibitors of Wnt targets are being explored as primary or adjuvant chemotherapy. In this study, we have investigated the ability of FH535, an antagonist of Wnt signaling, to inhibit the growth of osteosarcoma cells. We found that FH535 was cytotoxic in all osteosarcoma cell lines which were tested (143b, U2OS, SaOS-2, HOS, K7M2) but well tolerated by normal human osteoblast cells. Additionally, we have developed an in vitro model of doxorubicin-resistant osteosarcoma and found that these cells were highly responsive to FH535 treatment. Our analysis provided evidence that FH535 strongly inhibited markers of canonical Wnt signaling. In addition, our findings demonstrate a reduction in PAR-modification of Axin2 indicating inhibition of the tankyrase 1/2 enzymes. Moreover, we observed inhibition of auto-modification of PARP1 in the presence of FH535, indicating inhibition of PARP1 enzymatic activity. These data provide evidence that FH535 acts through the tankyrase 1/2 enzymes to suppress Wnt signaling and could be explored as a potent chemotherapeutic agent for the control of osteosarcoma.